ANALISIS STABILITAS HARGA BAHAN POKOK DI PASAR TRADISIONAL KOTA SURAKARTA DI ERA E-COMMERCE - Sulistyowati Sulistyowati; Yuni Safitri (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2026)
Price stability of staple commodities is a crucial aspect in maintaining economic balance as it directly affects consumers’ purchasing power and trading activities. Traditional markets face price instability due to supply-demand dynamics, distribution factors, production conditions, and e-commerce-driven consumer behavior changes. This study aims to analyze the stability of staple commodity prices in traditional markets in Surakarta City during the e-commerce era and identify factors influencing price changes. This research employed a descriptive qualitative method using a field study approach through observations and interviews with traditional market actors. The analysis was based on price stability theory, supply and demand theory, price volatility, distribution and supply chain perspectives, and digital transformation theory. The findings reveal that staple commodity prices in traditional markets in Surakarta City elatively unstable, particularly for commodities vulnerable to production and distribution changes, such as chili, cooking oil, and eggs. Price instability is mainly influenced by distribution disruptions, weather changes, transportation costs, and seasonal demand increases. E-commerce contributes to greater price transparency and market competition while influencing consumer behavior toward traditional markets. This study concludes that integrating traditional market systems with digital technology is an important strategy for improving price stability in the future.